The comparation of cultural dimention between Sulawesi, Indonesia and Philippine: a measurement of five Indonesian islands - R Setyaningrum; A R Wijaya; Subagyo Subagyo (Institut Teknologi Sepuluh Nopember, 2018)
The Indonesian archipelago is bordered by many countries, such as Sulawesi island bordered by the Philippines. The culture of Sulawesi allegedly had the same style with the culture of the Filipinos. Several studies have examined the details of Indonesian culture, especially the culture of Sulawesi and the Philippines, but has not studied the details of the cultural dimension measurement of both countries. This study aims to measure the dimensions of Hofstede cultural communities in the Indonesian archipelago and do a comparative study of cultural dimensions of Hofstede to Sulawesi and the Philippines. The data (631 respondents) was analysed using calculations score of Hofstede cultural dimensions consists of the Power Distance Index (PDI), Individualism (IDV), Masculinity (MAS), Long-term orientation (LTO) and Uncertainty Avoidance (UAI). The measurement results of Hofstede cultural dimensions Indonesia is slightly different from the predecessor research. There are several dimensions of Hofstede Indonesian culture which decreased compared to the results of research on the IBM Company, which consists of PDI, UAI, and LTO as well as an increase at IDV and MAS. The geographical position of the region of Sulawesi and the Philippines affect both cultural interactions. Several cultural dimension scores of Sulawesi and the Philippines were relatively close. It shows that Sulawesi and the Philippines have similar cultural dimensions PDI, IDV and MAS. This cultural dimension measurement results expected to contribute to the fields of science related to the cultural mapping of Indonesia and the Philippines.